Review of 1971/10/29 Concert at Barber Institute of Fine Arts (University of Birmingham) Lunchtime concert of works by Elgar, Tippett and Maxwell Davies, given by students from Birmingham University conducted by Keith Potter - Williamson, Laurence (Contact: A Journal for Contemporary Music (1971-1990), 1971)